The Impact of Internet of Things (IoT)-Driven Digital Transformation on Workforce Dynamics in Facilities Management - Palanisamy, Tarani a/p; Sarpin, Norliana; Md. Gharip, Nor Hazlin; Omar, Roshartini; Sallehuddin, Aina Mardia; Goh, Kai Chen (Research in Management of Technology and Business, 2026)
The rapid integration of Internet of Things (IoT) technologies is transforming facilities management (FM) in Malaysia, shifting operations from reactive, manual tasks to proactive, data-driven practices. This study investigates the impact of IoT adoption on workforce dynamics, identifies the challenges faced by FM employees, and explores strategies for managing workforce transitions in Kuala Lumpur. A quantitative descriptive approach was employed, collecting data from 111 FM employees which represents 85.38% response rate across roles such as technicians, engineers, supervisors, and managers. The findings reveal that IoT adoption significantly enhances workforce efficiency, collaboration, and data-driven decision-making while reshaping roles and skill requirements. Key challenges identified include job displacement, organizational resistance, skill gaps, and cybersecurity concerns, which may hinder effective adaptation. To address these challenges, respondents emphasized the importance of comprehensive upskilling programs, practical hands-on training, cross-department collaboration, clear management communication, skills assessment, incentive systems, and cybersecurity awareness initiatives. The study highlights the need for a human-centered approach to digital transformation, integrating employee development with technological implementation to ensure a smooth and sustainable transition. These insights provide practical recommendations for FM organizations, policymakers, and training providers to enhance workforce readiness, engagement, and adaptability, contributing to the successful adoption of IoT-driven operations and the advancement of smart building initiatives in Malaysia.